Effects of powder compression and laser re-melting on the microstructure and mechanical properties of additively manufactured parts in laser-powder bed fusion - Muhannad Ahmed Obeidi; Alex Conway; Andre Mussatto; Merve Nur Dogu; Sithara P. Sreenilayam; Hasan Ayub; Inam Ul Ahad; Dermot Brabazon (Results in Materials, 2022)
Achieving good surface profile and low levels of porosity are prime challenges in the Laser-Powder Bed Fusion (L-PBF) additive manufacturing technique. In order to optimise these properties, post-processing is often required. However, the compression of powder spread on the build plate and re-melting of each build layer during the L-PBF process could address these challenges. In this study, the effect of different powder compression ratios and laser re-melting regimes on the density, microstructure morphology, surface profile and mechanical properties of L-PBF produced parts were investigated. Two different metal printers with same laser processing parameters were used to fabricate 10 × 10 × 10 mm3 stainless steel 316L samples. To examine the impact of compression ratio and layer re-melting, one set of samples was prepared with three different compression levels for each layer and a second set of samples either a single or double set of laser passes for each layer. The Volumetric Energy Density (VED) range examines was from 26.7 J/mm3 to 80 J/mm3. Density, hardness, elastic modulus, microstructure and surface profiles of the printed samples were characterised. A 3% increment in density and a 50% reduction in the surface roughness were achieved using a laser double pass over each layer. The results demonstrate, by applying different powder compression ratios onto the powder bed and by re-melting each layer, that the density, surface roughness and the elastic modulus of the produced samples can be improved.